FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI ANGGOTA KOPERASI DAN KESEJAHTERAAN ANGGOTA PADA KOPERASI UNIT DESA (KUD) DI KABUPATEN JEMBRANA - Catur, I Ketut; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.12.TAHUN 2018, 2018)
Factors of low quality of human resources that have an impact on the management of organization and business; members of the cooperate are generally small people, so it's pretty hard to empower them; the low participation of members that is visible from the small amount of paid-up capital of members and Member utilization of services business cooperate; the location of the cooperation tend to be less/no strategic for business; as well as the culture of the Organization cooperate that is less conducive to developing the business. This research aims to analyze the influence of cooperate knowledge, the ability of administrators, service cooperatives, cooperate interest and participation of the members of the cooperative in the cooperate against the welfare of society in Jembrana Regency, analyzed with partial least square (PLS). The location of the research done in Jembrana Regency. Types of data used in this research is quantitative and qualitative. The source of the data used in this research is the primary data from the results of the questionnaire to respondents.    The results of the analysis showed that n knowledge, the ability of administrators, service quality of cooperation and interest in cooperate on the positive and significant participation of influential members of the village Jembrana Regency. Cooperate knowledge, the ability of the Executive Board, and the Ministry of cooperatives was not significant effect against the welfare of society, while the interest and participation of the members of the cooperative in the village of positive and significant effect against community welfare in Jembrana Regency. The participation of members of the cooperative in the village mediated significantly influences the ability of the Executive Board, the Ministry of cooperation and interest in cooperate  against the welfare of the community, but the influence of perkoperasian knowledge against the welfare of society mediated by the insignificant participation of members of the cooperative in the village Jembrana Regency.